2019
DOI: 10.5815/ijmecs.2019.08.05
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning based Approach for Mapping Personality Traits and Perceived Stress Scale of Undergraduate Students

Abstract: This paper focuses on the personality traits of students and stress scale they had to face in undergraduate level. With the advancement of computer science and machine learning based applications, we have tried to inter-correlate the terms. In the area of computational psychology, it is important to understand participants' psychological behavior using personality traits and predict how he/she is going to react on a certain level of the stressed situation. For the experiment, we have collected data of around 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…They found that extroverted people tend to get moderately stressed, while introverted people tend to have lower stress. In the data collection, they also found that 30 people responded with low stress, 18 with high stress, and 114 with moderate stress (18). There is a noticeable difference between university players in academics and those balancing both sports and academics.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that extroverted people tend to get moderately stressed, while introverted people tend to have lower stress. In the data collection, they also found that 30 people responded with low stress, 18 with high stress, and 114 with moderate stress (18). There is a noticeable difference between university players in academics and those balancing both sports and academics.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have focused on the impact of collegiate athletes in D1, D2, and D3 colleges, presenting that argument of the mental health and its impact on students (4). Gaston-Gayles conducted their studies by using motivation as a measurement to predict collegiate athletes' success in Manasvi Shah 1 , Alexis Anderson-Urriola 2 Journal of Emerging Investigators • www.emerginginvestigators.org https://doi.org/10.59720/23-133 (18,19). They found that extroverted people tend to get moderately stressed, while introverted people tend to have lower stress.…”
Section: Introductionmentioning
confidence: 99%
“…Исследование того, как может меняться алгоритм решения однотипных задач при изменении сложности их исходных данных, имеет большое значение при разработке систем искусственного интеллекта. В работах этого направления, например в [Popov et al, 2010;Kant, 2012;Karamath Ali, Amalarethinam, 2013;Fischer, Plessow, 2015;Ajay, Singh, 2015;Tran, Le, 2015;Nandi et al, 2018;Marouf et al, 2019], важно не только научить машину решать некоторый класс задач, но и приблизить работу машины к способам решения аналогичных задач человеком. Для решения этой проблемы необходимо сочетать работы в области совершенствования технических систем с исследованиями в инженерной психологии.…”
Section: Introductionunclassified
“…На использование человеком параллельных стратегий при решении различных задач указывают многие авторы психологических исследований [Popov et al, 2010;Kant, 2012;Karamath, Amalarethinam, 2013;Fischer, Plessow, 2015;Ajay, Singh, 2015;Tran, Le, 2015;Nandi et al, 2018;Marouf et al, 2019]. Во всех случаях можно говорить о формировании в мозге человека специальных структур в процессе решения серии задач одного типа.…”
Section: Introductionunclassified